Systematic perspectives on the distinction between appearances and things in themselves in the Critique of Pure Reason - Klein, Joel T. (Studia Kantiana, 2023)
In this paper I argue that in the first Critique and in the Prolegomena Kant's distinction between Appearances and Things in themselves do not belong to a single, one-dimensional system, but actually entails six different layers. Each layer has a particular perspective on the concept of things in themselves, which is used for drawing specific boundaries regarding appearances and is related to a particular kind of illusion. I also argue that these six different meanings of things in themselves are systematically articulated according the broader use of reason in its theoretical and practical field.